2015
DOI: 10.1002/brb3.355
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Gabra4 expression during alcohol withdrawal is mediated by specific microRNAs in cultured mouse cortical neurons

Abstract: BackgroundAlcohol abuse and dependence are a serious public health problem. A large number of alcohol-regulated genes, (ARGs) are known to be influenced by alcohol use and withdrawal (AW), and recent evidence suggests that neuroadaptation to alcohol may be due in part to epigenetic changes in the expression of ARGs. Gabra4, which encodes the α4 subunit of GABAA receptors (GABAARs), is one of a number of ARGs that show remarkable plasticity in response to alcohol, being rapidly upregulated by acute alcohol expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The expression level of lncRNAs is highest in brain (Derrien et al, 2012), and similar to protein-coding genes; they are regulated by neuronal activity (Barry et al, 2014) and show cell type- and brain region-specific expression patterns (Belgard et al, 2011; Mercer, Dinger, Sunkin, Mehler, & Mattick, 2008), suggesting that their expression is important in discrete CNS functions. Although the physiological roles of lncRNAs are still emerging, they appear to be involved in cis-regulation of neighboring genes (Goff et al, 2015; Zuo et al, 2016) and the regulation of gene expression involved in adaptive behavior (Bekdash & Harrison, 2015; Spadaro et al, 2015). The extent to which specific lncRNAs contribute to the development and maintenance of alcohol- or other substance-abuse disorders is currently an under-investigated area, with the potential to uncover novel regulatory gene networks involved in the addictive process.…”
Section: Long Non-coding Rnamentioning
confidence: 99%
“…The expression level of lncRNAs is highest in brain (Derrien et al, 2012), and similar to protein-coding genes; they are regulated by neuronal activity (Barry et al, 2014) and show cell type- and brain region-specific expression patterns (Belgard et al, 2011; Mercer, Dinger, Sunkin, Mehler, & Mattick, 2008), suggesting that their expression is important in discrete CNS functions. Although the physiological roles of lncRNAs are still emerging, they appear to be involved in cis-regulation of neighboring genes (Goff et al, 2015; Zuo et al, 2016) and the regulation of gene expression involved in adaptive behavior (Bekdash & Harrison, 2015; Spadaro et al, 2015). The extent to which specific lncRNAs contribute to the development and maintenance of alcohol- or other substance-abuse disorders is currently an under-investigated area, with the potential to uncover novel regulatory gene networks involved in the addictive process.…”
Section: Long Non-coding Rnamentioning
confidence: 99%
“…Both glutamatergic and GABAergic synapses are thought to be strongly involved in mediating the effects of alcohol [7], particularly via the NMDA-type of glutamate receptor and the alpha4-subunit containing GABA(A) receptor [8,9,10]. Both GABAergic and glutamatergic signalling systems, including the two types of receptors mentioned above, are altered in alcoholism [11,12,13,14]. Interestingly, it is not only the synaptic receptors which are affected by alcohol but also the neurotransmitter-inactivating mechanisms that are changed in alcoholic brains, particularly in the case of glutamatergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%
“…[19] and receptors [20,21]) sequestered behind such barrier would seem to imply that a signalling apparatus, possibly involving germ cells and sperm, both in their mature and immature forms either dormant or active and mediated by L-glutamate, exists and functions in testes. Glutamate transporters would then provide a regulating ("inactivating") mechanism analogous to that functioning at brain synapses (reviews: [12,13). Alternatively, Lglutamate transport, mainly by GLAST (EAAT1) and EAAT5 could trigger chloride influx thus hyperpolarizing and activating the sperm [21].…”
Section: Introductionmentioning
confidence: 99%
“…These differences are likely to yield GABA A receptors with distinct pharmacological and functional characteristics (reviewed in Dick et al, ). The mechanism by which this occurs is not known, but previous studies have shown that the expression of selected GABA A receptor subunit can be selectively altered by miRNAs (Bekdash and Harrison, ; Zhao et al, ).…”
mentioning
confidence: 99%
“…Some of these miRNAs selectively target isoforms of GABA A receptors to manipulate their expression. Specifically, miR‐181, miR‐216, and miR‐203 directly target the α1 subunit (Zhao et al, ), and miR‐155, miR‐186, miR‐24, miR‐27b, and miR‐375 directly target the α4 subunit (Bekdash and Harrison, ). Of these, only 1 miRNA, miR‐203, is up‐regulated in the prefrontal cortex of human alcoholics (Lewohl et al, ).…”
mentioning
confidence: 99%